2005
DOI: 10.1364/opex.13.001085
|View full text |Cite
|
Sign up to set email alerts
|

Gain-switched Tm3+-doped double-clad silica fiber laser

Abstract: A gain-switched Tm-doped double-clad silica fiber laser operating at a wavelength of approximately 2microm with moderate output energy of 14.7mJ per pulse and a slope efficiency of 39.5% (with respect to launched pump energy) is realized pumped at 1.064microm from a Nd:YAG laser. The gain-switched fiber laser pulses are built up by a series of relaxation spikes, and every spike pulse duration is nearly 1micros. The output wavelength becomes longer, and the slope efficiency increases with the increase in fiber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 0 publications
2
28
0
Order By: Relevance
“…2(b). These phenomena were also observed in previous studies [3], [8]. Considering a typical ytterbium-doped fiber amplifier with 2-m long under 1-W pump power, a shorter fiber was chose for avoiding Raman effect [10] and typical pump power of commercial device for preamplifier.…”
Section: Wpa-29supporting
confidence: 62%
“…2(b). These phenomena were also observed in previous studies [3], [8]. Considering a typical ytterbium-doped fiber amplifier with 2-m long under 1-W pump power, a shorter fiber was chose for avoiding Raman effect [10] and typical pump power of commercial device for preamplifier.…”
Section: Wpa-29supporting
confidence: 62%
“…-doped fibers have recently attracted much interest due to their potential application in material processing, laser sensing, free-space optical communication, and bio-medical (Modsching et al 2011;Creeden et al 2014;Tang et al 2010;Zhang et al 2005a;Liu et al 2013;He et al 2013). Lots of studies have been demonstrated to obtain high power fiber laser (Goodno et al 2009;Schellhorn et al 2009; http://www.laserfocusworld.com/articles/ print/volume-48/issue-08/features/holmium-doped-silica-fiber-designs-extend-fiber-lasersbeyond-2-um.html) or pumped light source for generating the longer laser wavelength with Ho 3?…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the gain-switching technique has its own advantages, including the simplicity in operation and extreme flexibility in pulse repetition rate and width tuning [10], while the Qswitching technique is typically limited by low repetition rate or pulse width in addition to the need for the bulk Q-switching device [11]. Recently, the gain-switching technique has been successfully adopted to obtain 2 μm pulses reported in lots of literature [12][13][14]. However, when these gain-switched TDFLs are pumped around 790 nm or 1 μm, the output pulses consist of a series of unstable chaotic relaxation spikes as the result of the long relaxation time (>10 μs) from the pump energy level to the laser emission 2 μm band [12,13].…”
Section: Introductionmentioning
confidence: 99%